Association of Psoriasis With Anxiety and Depression: A Case–Control Study in Chinese Patients - Jing, Danrong; Xiao, Hui; Shen, Minxue; Chen, Xiang; Han, Xi; Kuang, Yehong; Zhu, Wu; Xiao, Yi (Frontiers in Medicine, 2021)
Background: Patients with psoriasis are prone to suffer from anxiety and depression during their lifetime. This study aimed to investigate the association of psoriasis with anxiety and depression in Chinese patients. Methods: A case-control study in Chinese patients with psoriasis vulgaris and healthy controls was conducted. Clinical information based on patient-reported, clinical information, and reliable structured questionnaires were collected. Multivariable logistic regression was used to investigate the associations, in terms of adjusted odds ratios (AORs). Results: We continuously selected 1571 patients who were firstly diagnosed with psoriasis vulgaris, and 1571 healthy controls, matched by age and sex. The risk of depression in the psoriasis vulgaris group was higher than that in the healthy controls (AOR=1.30, P=0.047), while no differences were found in the risk of anxiety between the two groups (AOR=1.18, P=0.381). Subgroup analysis by disease onsets showed that late-onset psoriasis (LOP) was significantly associated with a higher risk of anxiety (AOR=1.47, P=0.033) and depression symptoms (AOR=1.85, P=0.012) but not with early-onset psoriasis (EOP). Subgroup analysis by disease severity indicated that no difference was observed in the associations of mild psoriasis vulgaris, moderate-to-severe psoriasis vulgaris with anxiety and depression. Conclusion: Patients with psoriasis vulgaris were more likely to develop depression compared with the general population. LOP patients were positively associated with anxiety and depression. We believe the screening of emotional disorders should be included in the daily management of psoriasis patients.